THE INFLUENCE OF FINANCIAL LITERACY, PERCEIVED BENEFITS, AND SOCIAL INFLUENCES ON INTEREST IN USE OF ILLEGAL FINTECH LENDING - Karina Lintang Ayu Salindri; Dyah Ratnawati (Yayasan Education and Social Center, 2023)
The increasing presence of fintech in social life reflects the annual changes in people's lifestyles, as the surrounding environment is predominantly occupied by information technology users who consider it a necessity for their daily lives. The objective of this study was to examine the influence of financial literacy, perceived benefits, and social influences on individuals' inclination to engage in illegal lending through fintech platforms. This research adopts a quantitative approach, with a sample size of 100 students from the Faculty of Economics and Business at UPN